2012
DOI: 10.1371/journal.pone.0041457
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Small D-Enantiomeric Alzheimer’s Amyloid-β Binding Peptide Ligand for Future In Vivo Imaging Applications

Abstract: Alzheimer’s disease (AD) is a devastating disease affecting predominantly the aging population. One of the characteristic pathological hallmarks of AD are neuritic plaques, consisting of amyloid-β peptide (Aβ). While there has been some advancement in diagnostic classification of AD patients according to their clinical severity, no fully reliable method for pre-symptomatic diagnosis of AD is available. To enable such early diagnosis, which will allow the initiation of treatments early in the disease progress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…It is crucial to highlight that this value is only an overall estimate of binding affinity across the entire spectrum of oligomers present in the oA␤42 preparation, which is a heterogeneous mixture of aggregates. The best fit occurred for a 1:1 binding model with drifting baseline correction ( 2 ϭ 0.214) and yielded a K D value of low micromolar value (11 M), indicating a moderate affinity between the 15M S.A. peptide and oA␤42, and similar to other reports of A␤-peptide interactions (34).…”
Section: M Sa Binds Pre-formed A␤42 Oligomers As Shown By Surfacsupporting
confidence: 85%
“…It is crucial to highlight that this value is only an overall estimate of binding affinity across the entire spectrum of oligomers present in the oA␤42 preparation, which is a heterogeneous mixture of aggregates. The best fit occurred for a 1:1 binding model with drifting baseline correction ( 2 ϭ 0.214) and yielded a K D value of low micromolar value (11 M), indicating a moderate affinity between the 15M S.A. peptide and oA␤42, and similar to other reports of A␤-peptide interactions (34).…”
Section: M Sa Binds Pre-formed A␤42 Oligomers As Shown By Surfacsupporting
confidence: 85%
“…In this study we infused the hippocampus of Tg AD model mice for eight weeks with the small D-enantiomeric peptide D3 conjugated to FITC (D3- FITC) that has a high affinity for oligomeric Aβ 42 [23, 24, 26], and examined cognitive performance after 6.5 weeks, and the Aβ load after the end of the cognitive testing.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of D3 is described elsewhere [2427]. We chose to use D3-FITC (i.e., D3 conjugated with a FITC moiety via an additional C-terminal lysine; D3 sequence: rprtrlhthrnr) because we wanted to follow its fate in the animal and the FITC-label does, if at all, positively affect the D3 Aβ binding properties [30].…”
Section: Methodsmentioning
confidence: 99%
“…D1 peptide has the capacity to inhibit the Aβ peptide aggregation and to promote Aβ aggregates disaggregation. D1 is formed by D amino acids that are stable against endogenous proteases [12][13][14]. In the present research, we demonstrated that GNRs functionalized with the peptide D1 containing a spacer of polyethyleneglycol (PEG) (GNR-PEG-D1) promotes the enhancement of the fluorescence signal of CRANAD-2 associated with Aβ aggregates (Figure 3).…”
Section: Introductionmentioning
confidence: 58%
“…D1 peptide has the capacity to inhibit the Aβ peptide aggregation and to promote Aβ aggregates disaggregation. D1 is formed by D amino acids that are stable against endogenous proteases [12][13][14].…”
Section: Introductionmentioning
confidence: 99%